Kritik der Politischen Ökonomie im 21. Jahrhundert.: Zur neueren Debatte um das marxsche „Transformationsproblem“ - Büttner, Hans-Peter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
While the majority of the scientific community holds Marxian Value and Price Theory to be internally inconsistent because of the so-called “transformation problem”, these claims can be sufficiently refuted. The key to the solution of the “transformation problem” is quite simple, so this contribution, because it requires the rejection of simultanism and physicalism, which represent the genuine method of neoclassical economics, a method that is completely incompatible with Marxian Critique of Political Economy. Outside of the iron cage of neoclassical equilibrium economics, Marxian ‘Capital’ can be reconstructed without neoclassical “pathologies” and offers us a whole new world of analytical tools for a critical theory of capitalist societies and its dynamics.